Kompresi Data pada Oracle 9i - Irving Vitra Paputungan (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2005)
Most decision support systems usually involve large amounts of data stored in a few very large tables. Asthese systems evolve, the demand on disk space can grow quickly. In today's environment, data warehouses ofhundreds of terabytes have become increasingly common.This paper will show how The Compression in Oracle 9i Release 2 works. In order to build and managethe database well.